Charting the development of sport expertise: challenges and opportunities. Issue 1 (1st January 2018) - Farrow, Damian; Reid, Machar; Buszard, Tim; Kovalchik, Stephanie
ABSTRACT: This review poses three key issues that will progress our understanding of the sport expertise literature and its translational scientific impact. Primarily relying on research conducted in interceptive sport tasks, and to a lesser extent team sports, we review the perceptual-cognitive skills of sports experts and explore the challenge of designing a sufficiently representative task to examine expertise. We focus on the methodological challenges presented by the reciprocal relationship between players' action capabilities and their perceptual-cognitive skill. Second, we consider the need for a paradigm shift in the experimental approach used when examining the development of sport expertise. In short, a shift from traditional expert-novice designs to more prospective longitudinal designs that cross-sectionally track the development of expertise is discussed. The final issue considers how the volume of in situ data now collected provides a rich source of information that sport expertise researchers have only begun to consider and integrate with more traditional sport psychology research. We demonstrate how statistical approaches that have described the likely trajectories of expert performers on their journey toward expertise coupled with more traditional qualitative experimental approaches can provide useful insights into the development of psychological performance skills and more broadly sport expertise.